PRESIDENTS AND LEADERSHIP IN STRATEGIC PLANNING AT A UNIVERSITY - Mahdi, Sahed (Jurnal Mentari, 2011)
Salah satu faktor yang mempengaruhi kesuksesan masa depan universitas swasta dan negeri adalah kemampuan manajemen atau pimpinan institusi tersebut  dalam memformulasi  desain perencanaan strategis yang realistis dan inspiratif untuk untuk dicapai, di samping komitmen pimpinan institusi melaksanakan strategi tersebut. Dengan adanya perencanaan strategis yang baik,  pimpinan kampus mempunyai landasan berpijak dalam memimpin sebuah universitas yang dipimpin. Oleh karena itu, artikel ini membahas beberapa aspek penting dalam (strategic planning) yang umum diterapkan dalam dunia akademik. Salah satu hasil yang dapat disumpulkan adalah perlunya kesadaran dan kemampuan pimpinan kampus mengenali atau menggambar posisi kampusnya saat ini, dan mensinergikan sumber daya yang ada untuk mencapai visi kampus yang ditetapkan.     Kata kunci: pimpinan, kepemimpinan, perencanaan strategis     REFERENCES     Alfred, R. L. (2005). Managing the big picture in colleges and universities: From tactics to strategy. Westport, CT: Praeger. Bargh, C., Bocock, J., Scott, P., & Smith, D. (2000). University Leadership: The role of the chief executive. Philadelphia: The Society for Research into Higher Education & Open University Press. Bean J. P, & Kuh G. D. (1984). A typology of planning problems. Journal of Higher Education, 55(1), 35-55. Beatty, E. R., & Blau, P. (1973). The organization of academic work. New York: Wiley and Sons. Calareso, J. P. (2007, July-September). Successful processes to engender board ownership of strategic planning. Planning for Higher Education, 12-21. Dill, D. D. (1996). Academic planning and organizational design: Lessons from leading American universities. Higher Education Quarterly, 50(1). Flawn, P. T. (1990). A primer for university presidents: Managing the modern university. Austin, TX: University of Texas Press. Gumport, P. J. (2003). The demand-response scenario: Perspectives of community college presidents. The ANNALS of the American Academy of Political and Social Science, 586, 38-57. Haas, R. M. (1997). Organizing the elements of planning. In Peterson, M. W. & Associates (Eds.), Planning and management for a changing environment: A handbook on redesigning postsecondary institutions (pp. 246-263). San Francisco: Jossey-Bass. Higgins, J. (1983). Public relations’ role in strategic planning for higher education. In M. S. Ensign & L. N. Adler (Eds.), Strategic planning contemporary viewpoints (pp. 181). Santa Barbara, CA: ABC-Clio, Inc. Keller, G. (1995). The vision thing in higher education. Planning for Higher Education, 23, 354-360. Keller, G. (1997). Examining what works in strategic planning. In Peterson, M. W. & Associates (Eds.), Planning and management for a changing environment: A handbook on redesigning postsecondary institutions (pp. 158-170). San Francisco: Jossey-Bass. Massey, W. F. (1994). Measuring performance: How colleges and universities can set meaningful goals and be accountable. Measuring Institutional Performance in Higher Education. Princeton, NJ: Peterson’s Guides. McClay, W. M. (2007). George Keller: Intellectual whirlwind. Chronicle of Higher Education, 54(13), B12. Millett, J. D. (1980). Management, governance, and leadership. New York: Amacom. Millett, J. D. (1976). The multiple roles of college and university presidents. (Office of Leadership Development in Higher Education). Washington, DC: American Council on Education. Morrison, J. L. (1992). Environmental scanning. In M. A. Whiteley, J. D. Porter, & R. H. Fenske (Eds.), The Primer for Institutional Research, Revised Edition, Association for Institutional Research. Neumann, A., & Larson, R. S. (1997). Enhancing the leadership factor in planning. In M. W. Peterson & Associates (Eds.), Planning and management for a changing environment: A handbook on redesigning postsecondary institutions (pp. 191-203). San Francisco: Jossey-Bass. Opatz, P., & Hutchinson, K. (Winter, 1998-99). Building trust through strategic planning. Planning for Higher Education, 27, 21-27. Perlman, B., Gueths, J., & Weber, D. A. (1988). The academic intrapreneur: Strategy, innovation, and management in higher education. New York: Praeger. Page, R. (2007). Leadership as place. In Wergin, J. F. (Ed.), Leadership in place: How academic professionals can find their leadership voice (pp. 192-223). Bolton, MA: Anker Publishing Company, Inc.   Rowley, D. J., Lujan, H. D., & Dolence, M. G. (1997). Strategic change in colleges and universities. San Francisco: Jossey-Bass. Ruben, B. D. (2005, August). The center for organizational development and leadership at Rutgers University: A case study. Advances in Developing Human Resources, 7(3), 368-395. Schmidtlein, F. A., & Milton, T. H. (1998-1999). College and university planning: perspectives from a nation-wide study. Planning for Higher Education, 17(3), 107-119. Schuster, J. H., Smith, D. G., Corak, K. A., & Yamada, M. M. (1994). Strategic governance: How to make big decisions better. Phoenix, AZ: American Council on Education and The Oryx Press. Weingartner, R. H. (1996). Fitting form to function: A primer on the organization of academic institutions. Phoenix, AZ: American Council on Education and The Oryx Press. Wilson, R. (2008). At Drake, leadership by example is effective. Chronicle of Higher Education, 54(45), B9.